Environmental impact assessment methodologies regarding traffic noise in Portugal - A Carvalho (1996)
Few years after the beginning of the use of Environmental Impact Assessment (EIA) studies regarding traffic noise in Portugal it is time to analyze the accomplishment of these environmental policies and the way these studies have been done. The purpose of this paper is to present the preliminary results concerning a research project about noise in Environmental Impact Assessment. The scope of this research is to investigate and characterize methods of analysis regarding noise in the assessment of environmental impact and their influence in the built surrounding due to the construction of new roads and highways. The goal is to study the methodologies of EIA studies that have been used in Portugal and eventually to adapt them to the Portuguese legal particularities that this subject implies in the particular area of noise. This paper presents the main methods that have been used throughout Portugal, achieved by the analysis of the main EIA studies done in the near past. The methodologies presented result from the analysis made to the studies requested by the National Road Services - Ministry of Equipment, Planning and Territorial Administration (JAE-MEPAT) and the Portuguese Highway Central Authority (BRISA). In summary, this project intends finally to systematize the major practices used in Portugal and eventually to propose a new and consistent Environmental Impact Assessment methodology to assess traffic noise in new roads or highways.